René Antoine Ferchault de Réaumur (1683–1757), a naturalist and pioneer of acarology and his contacts with Poland - Daszkiewicz, Piotr (Biological Letters, 2017)
René Antoine Ferchault de Réaumur was one of the most important scientists of the Age of Enlightenment. His relations with Polish scientists are analysed, with particular reference to Franciszek Bieliński (Grand Marshal of the Crown), Konstanty Franciszek Fremel (a Saxon specialist of glass technology in Poland), and Johann Ernst Stieff (a Silesian scientist). Réaumur’s work on mites is discussed in the context of his entomological publications. For the first time, illustrations of mites drawn by Claude Aubriet (from Réaumur’s collection) are reproduced here.